Belgium : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses the Observance of Standards and Codes and Financial Action Task Force (FATF) Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) in Belgium. In Belgium, the financial intelligence unit (CTIF-CFI) has noted a shift in money laundering activities in recent years. It has emerged that the proportion of new cases involving layering operations and, to a lesser extent, integration, is on the rise. At the layering stage, the methods favored by criminals are national or international payments via wire transfers or cheques, as well as remittance transactions.